Selective Hydrogenation of Furfural: Pure Silica Supported Metal Catalysts. Issue 9 (2nd March 2022) - Zhang, Min; Yang, Jing‐He
Abstract: Furfural is a raw material for the preparation of furan derivatives with active chemical properties. Due to its ability to prepare various high value‐added chemicals through oxidation, condensation, hydrogenation, and other reactions, furfural has received extensive attention. The activity of catalyst depends largely on the solvent effect, reaction temperature, metal‐support interaction, metal nanoparticle size, and also depends on the synthesis method of catalyst. In this review, mono‐metal (Cu, Co, Ni, Fe, Zn, Zr, Au, Pt, Pd, etc.) and bimetallic (Cu−, Ni−, Pt− and Pd−, etc.) catalysts supported on mesoporous silica materials for the hydrogenation of furfural to various high value‐added chemicals in gas or liquid phase are highlighted. At the same time, some feasible suggestions are put forward. Mono‐metal catalysts are prone to deactivation (due to carbon deposition and metal sintering), and the addition of a second metal or solvent modification can be used to improve catalyst activity, furfural conversion, and product selectivity. Abstract : Biomass is the sustainable source of organic compounds. Furfural is an important platform molecule of biomass and the natural precursor of furan‐based chemicals. In the review, the mono‐metal and bimetal metals (based on Cu, Ni, Fe, Zn, Au, Pt, and Pd) supported on pure silica such as SiO2 aerogel, MCM‐41, and SBA‐15 heterogeneous catalysts for selective hydrogenation of furfural to a variety of high value‐added chemicals are highlighted.